An all-optical Compton source for single-exposure x-ray imaging. (22nd January 2016) - Döpp, A; Guillaume, E; Thaury, C; Gautier, J; Andriyash, I; Lifschitz, A; Malka, V; Rousse, A; Ta Phuoc, K
Abstract: All-optical Compton sources are innovative, compact devices to produce high energy femtosecond x-rays. Here we present results on a single-pulse scheme that uses a plasma mirror to reflect the drive beam of a laser plasma accelerator and to make it collide with the highly-relativistic electrons in its wake. The accelerator is operated in the self-injection regime, producing quasi-monoenergetic electron beams of around 150 MeV peak energy. Scattering with the intense femtosecond laser pulse leads to the emission of a collimated high energy photon beam. Using continuum-attenuation filters we measure significant signal content beyond 100 keV and with simulations we estimate a peak photon energy of around 500 keV. The source divergence is about 13 mrad and the pointing stability is 7 mrad. We demonstrate that the photon yield from the source is sufficiently high to illuminate a centimeter-size sample placed 90 centimeters behind the source, thus obtaining radiographs in a single shot.